Study on the underpinning mechanisms of microwave-induced synthesis of carbon-coated metal nanoparticles - Jia, Pingshan; Sun, Jing; Wang, Wenlong; Song, Zhanlong; Zhao, Xiqiang; Mao, Yanpeng (Frontiers in Energy Research, 2023)
Microwave-induced metal arc discharge provides an intriguing solution for the synthesis of carbon-coated metal nanoparticles (M@CNPs) due to its fast formation and improved quality of products, however, the underpinning reaction mechanism is not comprehensively revealed. In this work, the effect of arc discharge intensity on the product morphology is firstly investigated by adjusting microwave power. And then, the effects of the organic groups (i.e. cyclopentadienyl v. s Acetylacetonate groups) and metal catalysis on the product morphology are also investigated by selecting ferrocene, iron acetylacetonate, nickelocene, and nickel acetylacetonate as precursors. Specifically, moderate microwave power can not only destroy the precursor to form carbon nanosheets by inducing intense discharge heat release but also provide sufficient intermittency to allow the carbon nanosheets to deposit on the surface of the metal core, which is an important precondition in fabricating M@CNPs. The structure of organic groups in the precursor also plays a predominant role in adjusting product morphology. Cyclopentadienyl groups tend to encapsulate the metal core to form graphitized carbon shells as the coordination bond between cyclopentadienyl and metal is recognized as a very strong covalent bond that confines the cyclopentadienyl collapse to metal core, and the cyclic structure facilitates the formation of graphite. In contrast, the acetylacetonate groups intend to combine randomly due to their open-loop structure. Moreover, for open-loop structures such as acetylacetonate groups, metal catalysis also affects the growth trend, of which Ni is more likely to induce the formation of carbon nanotubes relative to Fe. This work can provide a good reference for the synthesis of M@CNPs with controllable morphology.